2018
DOI: 10.1039/c8nj01062e
|View full text |Cite
|
Sign up to set email alerts
|

Structure-enhanced removal of Cr(vi) in aqueous solutions using MoS2 ultrathin nanosheets

Abstract: Molybdenum disulfide (MoS2) ultrathin nanosheets with enlarged interlayer spacing and defects enables the structure-enhanced removal of Cr(vi), in which the synergistic effects of adsorption and reduction not only captured Cr(vi) from aqueous solutions, but also alleviated the toxicity of chromium to some degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…65,210−212 It is reported that 1T MoS 2 exhibited the high adsorption capacity (200.3 mg/g), compared to 2H MoS 2 (70.7 mg/g) and M MoS 2 (82.8 mg/g, Figure 5A). 210 Sun et al reported that the maximum sorption capacity of Cr(VI) on pristine 2D MoS 2 via a facile one-step hydrothermal method was 84.03 mg/g, 213 which was slightly higher than the flowerlike nanostructures MoS 2 through a surfactant-assisted hydrothermal method (66.1 mg/g). 214 In order to increase the adsorption performance and redox capacity, various MoS 2based composites were widely synthesized in recent years.…”
Section: Environmental Applicationmentioning
confidence: 99%
“…65,210−212 It is reported that 1T MoS 2 exhibited the high adsorption capacity (200.3 mg/g), compared to 2H MoS 2 (70.7 mg/g) and M MoS 2 (82.8 mg/g, Figure 5A). 210 Sun et al reported that the maximum sorption capacity of Cr(VI) on pristine 2D MoS 2 via a facile one-step hydrothermal method was 84.03 mg/g, 213 which was slightly higher than the flowerlike nanostructures MoS 2 through a surfactant-assisted hydrothermal method (66.1 mg/g). 214 In order to increase the adsorption performance and redox capacity, various MoS 2based composites were widely synthesized in recent years.…”
Section: Environmental Applicationmentioning
confidence: 99%
“…It could be observed that the removal capacities of MXene and MXene-based composites toward metal ions in environment-related fields were significantly larger than those of other 2D materials, and many of them even surpassed graphene oxide for different aspects of environmental remediation. 19,50,73,80,81,[86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] To sum up, MXene as a heavy metal ion adsorbent has the advantages of excellent removal performance, rapid kinetics, high selectivity, extremely low heavy metal ion effluent, and reversible adsorption properties. (1) For excellent removal performance, as shown in Table 1, the maximum adsorption capacities of alkalization-MXene, Ti 3 C 2 T x -10% (Ti 3 C 2 T x was treated by 10% HF solutions), delaminated-MXene are about 140.10 mg g −1 for Pb(II), 19 250 mg g −1 for Cr(VI), 73 and 78.45 mg g −1 for Cu(II), 80 respectively.…”
Section: Heavy Metal Ion Removalmentioning
confidence: 99%
“…The adverse effect is caused by the competition between the HMs and other ions in the water for the active adsorption sites at the increased ionic strength [142]. Interestingly, MoS 2 can efficiently adsorb various cations and anions of HMs depending on the adsorption conditions [124], [126,130,131]. The effects of various anions and cations on the adsorption of HMs on MoS 2 are shown in Table 4.…”
Section: Molybdenum Sulfidesmentioning
confidence: 99%